Perbandingan Pemberian Pijat Oksitosin dan Pijat Effluerage Terhadap Kelancaran Asi di Wilayah Kerja Puskesmas Krawatwatu, Kota Serang, Kabupaten Banten - Neng Ticeu Noviyanti; Lili Farlihatun (Malahayati Nursing Journal, 2024)
ABSTRACT In 2020, the exclusive breastfeeding coverage in Serang Regency was 61.2% out of 11,128 infants, which was far below the target set by the Ministry of Health of 80%. One of the factors influencing the low coverage of exclusive breastfeeding is the insufficient production of breast milk in mothers. Non-pharmacological therapies such as oxytocin massage and effleurage massage are used to stimulate breast milk production. The study was objective to determine the difference in breast milk production between mothers who received oxytocin massage and those who received effleurage massage. The study employed an experimental research design with a pre- and post-test approach. The population consisted of all postpartum mothers with infants aged 0-6 months in the Krawatwatu Primary Health Center area, totaling 147 mothers. The sample size for each group, oxytocin massage and effleurage massage, was 25 mothers. Data were collected using a breast milk production questionnaire with the Gutman scale. Data analysis was performed using an independent t-test. Before oxytocin massage, 10 mothers (40%) had smooth breastfeeding while 15 mothers (60%) had difficulties. After oxytocin massage, 24 mothers (96%) had smooth breastfeeding, and only 1 mother (4%) experienced difficulties. Before effleurage massage, 11 mothers (44%) had smooth breastfeeding, while 14 mothers (56%) had difficulties. After effleurage massage, 20 mothers (80%) had smooth breastfeeding, and 5 mothers (20%) experienced difficulties. The t-test results showed a significance value of 0.008, which is less than 0.05. Therefore, the decision made was to accept the alternative hypothesis (Ha), indicating that there is a difference in breast milk production between mothers who received oxytocin massage and those who received effleurage massage in the Krawatwatu Primary Health Center area, Serang City, Banten Regency in 2023. There is a difference in breast milk production between mothers who received oxytocin massage and those who received effleurage massage in the Krawatwatu Primary Health Center area, Serang City, Banten Regency in 2023. Keywords: Massage, Oxytocin, Effleurage, Breast Milk.  ABSTRAK Di Kabupaten Serang pada tahun 2020 angka cakupan ASI ekslusif sebesar 61,2% dari 11.128 bayi atau jauh dari target dari Kementrian Kesehatan hingga 80%. Faktor yang mempengaruhi rendahnya cakupan ASI dimana salah satunya kurang lancarnya produksi ASI pada ibu. Upaya memperlancar produksi ASI adalah melalui terapi nonfarmakologi pijat oksitosin dan pijat effleurage. Penelitian ini bertujuan untuk mengetahui perbedaan kelancaran ASI pada ibu yang diberi pijat oksitosin dengan kelancaran ASI pada ibu yang diberi pijat effleurage. Penelitian ini bertujuan untuk mengetahui perbedaan kelancaran ASI pada ibu yang diberi pijat oksitosin dengan kelancaran ASI pada ibu yang diberi pijat effleurage. Hasil penelitian menunjukkan bahwa sebelum pijat oksitosin jumlah ibu dengan ASI lancar sebanyak 10 orang (40%) dan tidak lancar 15 orang (60%). Setelah pijat oksitosin jumlah ibu dengan ASI lancar sebanyak 24 orang (96%) dan tidak lancar 1 orang (4%). Sebelum pijat effleurage jumlah ibu dengan ASI lancar sebanyak 11 orang (44%) dan tidak lancar 14 orang (56%). Setelah pijat effleurage jumlah ibu dengan ASI lancar sebanyak 20 orang (80%) dan tidak lancar 5 orang (20%). Hasil uji t menunjukkan nilai sig. (0,008) 0,05. Keputusan yang diambil adalah menerima Ha, artinya terdapat perbedaan kelancaran ASI pada ibu yang diberi pihat oksitosin dengan ibu yang diberi pijat effleurage di Wilayah Kerja Puskesmas Krawatwatu, Kota Serang, Kabupaten Banten Tahun 2023. Terdapat perbedaan kelancaran ASI pada ibu yang diberi pihat oksitosin dengan ibu yang diberi pijat effleurage di Wilayah Kerja Puskesmas Krawatwatu, Kota Serang, Kabupaten Banten Tahun 2023. Kata Kunci: Pijat, Oksitosin, Effleurge, ASI.